PENERAPAN ALAT PENGURAI SABUT KELAPA DI MASYARAKAT NAGARI SUNGAI SARIAK PADANG PARIAMAN - Hendri Nurdin; Delima Yanti Sari; Toto Sugiarto; Purwantono Purwantono; Hastuti Hastuti (LPPM Institut Pendidikan Nusantara Global, 2026)
Coconut is a plantation commodity that has economic value. The process of stripping coconut grains will leave abundant coconut fiber as waste. Coconut coir waste is partly used by farmer groups in Nagari Sungai Sariak as fuel which causes thick smoke and air pollution so that it becomes a problem and must be resolved. The solution is done by applying a coconut fiber decomposer tool so that creativity and productivity are built. The success of the application of a coconut coir decomposer tool that uses an 8.5 PK diesel motor drive and a 2600 rpm rotation which has a capacity of 51 kg / hour. The effectiveness of the tool reaches 95% in decomposing coconut fiber in a short time. The production of cocofibre is utilized with a touch of advanced processing by the community for guest chair upholstery fillers, foot mat materials and so on. The application of science and technology can have an impact on improving the welfare and empowerment of the community. In addition, building community awareness in Nagari Sungai Sariak has an impact on responsible production within the community.